Hierarchical coordination framework in supply chain negotiations - Özdemir, Murat. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1999., 1999)
This study examines a hierarchical coordination framework between a supplier of a strategic item and his buyers in an environment where a mutual information exchange between the supplier and buyers is possible. A organizational hierarchical structure is defined via a generic supply chain contract where the supplier is in the leadership position. A three-level decision process is designed to help the supplier in making decisions: aggregate capacity planning, disaggregation of this aggregate capacity among the buyers and then price determination. Since the pricing model is a mixed integer nonlinear problem that is not easy to solve by exact methods, as a pioneering effort in supply chain management, a global metaheuristic algorithm SUPRIME (SUpply PRIce MEtaheuristic) is developed by integrating the principles of simulated annealing (SA) and tabu search (TS) procedures. Also the hierarchical structures in this study are mapped to Hierarchical Organization Planning (HOP) framework.
Keywords: Business logistics.